BokSmart: Pre-participation screening of rugby players by coaches based on internationally accepted medical standards - Patricios, JS; Collins, RM (South African Journal of Sports Medicine, 2010)
A comprehensive medical history forms a significant part of any medical assessment or screening. In the athlete, pre-participation screening is aimed at determining those aspects of personal and family history that place the participant at greater risk of sudden death, serious illness or musculoskeletal injury. In rugby union, where the incidence of head and neck injuries is higher than in other sports, emphasis needs to be placed on screening for potential risk factors for neurological injury. In a South African rugby environment, pre-season medical screening is not standard and indeed rarely practised. In most club and school settings, the rugby coach may well be the person most in contact with players and therefore in the best position to conduct an initial screening. This article reviews the relevant literature pertinent to such a guideline.